Podcasts im glottodidaktischen Medienverbund. Versuch einer vergleichenden Analyse - Adamczak-Krysztofowicz, Sylwia; Stork, Antje (Glottodidactica, 2009)
There is no doubt that the development of listening comprehension skills in foreign language learning is one of the least understood, least researched and yet, most important areas of foreign language teaching. In the light of this, the article aims to examine the usage and role of Podcasts in comparison with other didactic listening materials. The paper concludes with the discussion of possible technical and learning potential of podcasts for designing integrative training of listening comprehension.